Blunted Activation of Rho-Kinase in Yak Pulmonary Circulation. (14th January 2015) - Ishizaki, Takeshi; Mizuno, Shiro; Sakai, Akio; Matsukawa, Shigeru; Kojonazarov, Baktybek; Zamirbek, Baiserkeev; Umeda, Yukihiro; Morikawa, Miwa; Anzai, Masaki; Ishizuka, Tamotsu; Aldashev, Almaz
Abstract : Yaks have adapted to high altitude and they do not develop hypoxic pulmonary hypertension. Although we previously identified the important role of augmented nitric oxide synthase activity in the yak pulmonary circulatory system, evidence of the direct involvement of Rho-kinase as a basal vascular tone regulator is lacking. Four domesticated male pure-bred yaks and four bulls that were born and raised at an altitude of 3000 m in the Tien-Shan mountains were studied at an altitude of 3, 100 m. Mean pulmonary artery pressure (mPAP) was measured before and after fasudil (60 mg in 20 mL of saline) was intravenously administered using a Swan-Ganz catheter at a rate of 3.3 mL/min for 30 min. Fasudil decreased mPAP in bulls from 67.8 ± 14.9 to 32.3 ± 5.3  mmHg (P < 0.05 ) after 15 min and the level was maintained for 30 min, but it merely blunted mPAP in yaks from 28.2 ± 4.5 to 25.1 ± 11.1 and 23.2 ± 2.7  mmHg after 5 and 30 min, respectively. These findings comprise the first evidence of a modest role of Rho-kinase in the maintenance of pulmonary artery pressure in the yak.